Chorioamnionitis and neurodevelopmental outcome in very preterm infants from 2007 to 2017—a population‐based study. (20th December 2020) - Konzett, Karin; Riedl, David; Stark, Carmen; Simma, Burkhard
Abstract: Aim: The study compares neurodevelopmental outcome at 24 months corrected age of very preterm infants exposed to chorioamnionitis and controls. Peripartal parameters which may influence outcome are also investigated. Methods: In this observational population‐based study, very preterm infants born between 2007 and 2017 were eligible ( n = 466) and included if a histological placental examination and a complete neurodevelopmental assessment (Bayley Scale of Infant Development II or III) ( n = 168) were performed. Secondary analyses were calculated to identify peripartal factors that significantly influence mental and psychomotor outcome. Results: Included infants showed a mean MDI of 91.2 ( SD = 20.7) and a mean PDI of 99.4 ( SD = 14.8). Infants with ( n = 71) and without ( n = 97) chorioamnionitis did not statistically differ either with mean MDI (91.8 vs. 90.3 points; p = 0.29) or mean PDI (98.3 vs. 100.9 points; p = 0.81), even after controlling for gestational age, mean APGAR scores and administration of antenatal steroids. Bronchopulmonary dysplasia was identified as the most influential factor for both MDI ( p = .024) and PDI ( p = .004). Conclusion: We could not find an effect of chorioamnionitis on neurodevelopmental outcome of very preterm infants over an eleven‐year period. Analysis shows that postnatal factors have higher impacts than does chorioamnionitis.